Pop Up Book Media to Improve Student Learning Outcomes in Thematic Learning Theme of Objects Around Me in Class III State Primary School 064986 Medan - Yanisyah Intan Sari Siregar; Samsul Bahri (International Journal of Educational Research Excellence (IJERE), 2023)
This research aims to determine the effectiveness of applying pop up book media in improving student learning outcomes in thematic learning with the theme "Objects Around Me" . This research was carried out in class I II of SD Negeri 064986 Medan Amplas. This research is classroom action research . The subjects in this research were 23 students in class I II of SD Negeri 064986 Medan Amplas .The instruments and data collection techniques used in this research were observation and tests. From the results of observations, it is known that only 7 students scored above the Minimum Completeness Criteria (KKM) and 16 students below the KKM. The percentage of student learning outcomes only reached 30.43 %. After taking action in cycle I, there was an increase in student learning outcomes. The percentage of student learning outcomes in cycle I of the first meeting, namely 4 3 , 4 7%, the percentage of student learning outcomes in cycle I of the second meeting, namely 52 , 17 %. There was an increase in student learning outcomes by 21.74 % in cycle I, namely from 30.43 % at the time of observation to 52.17 % at the end of cycle I. The percentage of student learning outcomes in cycle II of the first meeting, namely 73.91 %, percentage student learning outcomes in cycle II of the second meeting, namely 8 6.95 %. There was an increase in student learning outcomes by 5 6.52 % in cycle II, namely from 30.43 % at the time of observation to 8 6.95 % at the end of cycle II. Thus it can be concluded that the use of pop up book media can improve learning outcomes for theme 3 " Objects Around Me " for class I II students at SD Negeri 064986.